Role of Facial Artery Musculomucosal Flap in Large and Recurrent Palatal Fistulae. (November 2013) - Shetty, Rahul; Lamba, Shashank; Gupta, Ashish Kumar
Objective: Palatal fistulas are not uncommon after palatoplasty. Although there are currently many techniques that can be used to close large palatal fistulae, most of these procedures are usually cumbersome and mostly unreliable with high recurrence rates. The facial artery musculomucosal (FAMM) flap was described to circumvent these problems. The purpose of this study was to review our experience with the FAMM flap to reconstruct palatal fistulas, most of them being recurrent. Materials and Methods: A retrospective analysis was done of 11 FAMM flaps performed between January 2007 and March 2012. Results: There were no major complications. Venous congestion was seen in two cases. Two flaps developed terminal marginal necrosis. One patient had suture line dehiscence. There were no recurrences of the fistula after repair. All patients had a satisfactory closure of the fistula. Conclusion: FAMM flap is a reliable and versatile flap that provides like with the like tissue and is a good option for closure of recurrent wide palatal fistulae.